Design and implementation of multi-user wireless body sensor networks - Afonso, José A. (2010)
This paper describes the development of two low power wireless body sensor network (BSN) prototypes that allow the real-time monitoring of wearable sensors data from multiple users with a single base station. The prototypes present differences in the architecture, wireless network hardware and implemented protocols. These systems integrate inertial sensors that allow the monitoring of users’ posture and goniometric development, as well as heart rate and respiratory rate sensors. The design of body sensor networks is challenging due to the requirements of quality of service provisioning and low energy consumption, combined in many cases with high traffic loads. The solutions presented in this paper address these challenges, with particular focus on the implemented medium access control protocols, which overcome some drawbacks presented by standard protocols when applied to BSN scenarios. The performance of the developed systems is presented, compared and discussed using theoretical, experimental and simulation methods. Results show that the proposed mechanisms provide good bandwidth efficiency and decrease the delivery error rate without significant increase in the energy consumption.